PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERILAKU KERJA INOVATIF GURU MELALUI IKLIM SEKOLAH DAN KETERLIBATAN KERJA SEBAGAI VARIABEL MEDIASI DI SEKOLAH XYZ TORAJA UTARA: [THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON TEACHERS' INNOVATIVE WORK BEHAVIOR THROUGH SCHOOL CLIMATE AND WORK ENGAGEMENT AS MEDIATING VARIABLES IN XYZ SCHOOL NORTH TORAJA] - Upi Julianto Poobos; Niko Sudibjo (Universitas Pelita Harapan, 2026)
This study aims to analyze the influence of transformational school leadership on teachers’ innovative work behavior (IWB), with school climate and work engagement serving as mediating variables. The study is grounded in the need for schools to continuously innovate in order to deliver relevant learning experiences, where leadership and teachers’ psychological conditions play crucial roles. The research was conducted with 60 teachers at XYZ School, North Toraja, employing a quantitative approach and path analysis using PLS-SEM. The findings show that transformational leadership has a positive effect on school climate, work engagement, and innovative work behavior. These results indicate that the principal’s support, vision, and exemplary conduct help create a positive work environment and foster teachers’ psychological energy. Furthermore, work engagement positively influences innovative behavior and serves as a mediator linking transformational leadership to teachers’ innovation. Conversely, school climate does not have a positive effect on innovative behavior and does not mediate the relationship. Overall, this study highlights that to promote teachers’ innovative work behavior, schools must strengthen humanistic and empowering transformational leadership practices and develop strategies that enhance work engagement as a foundational driver of innovation. Abstrak Bahasa Indonesia Penelitian ini bertujuan menganalisis pengaruh kepemimpinan transformasional kepala sekolah terhadap perilaku kerja inovatif (IWB) guru, dengan iklim sekolah dan keterlibatan kerja sebagai variabel mediasi. Latar belakang penelitian ini berangkat dari kebutuhan sekolah untuk terus berinovasi dalam menghadirkan pembelajaran yang relevan, peran kepemimpinan kepala sekolah dan kondisi psikologis guru menjadi faktor penting. Penelitian ini dilakukan pada 60 guru di sekolah XYZ Toraja Utara menggunakan pendekatan kuantitatif dan analisis jalur (PLS-SEM). Hasil penelitian menunjukkan bahwa kepemimpinan transformasional berpengaruh positif terhadap iklim sekolah, keterlibatan kerja dan perilaku kerja inovatif. Temuan ini mengindikasikan bahwa dukungan, visi, dan keteladan kepala sekolah mampu membangun suasana kerja yang positif serta menumbuhkan energi psikologis guru. Selain itu, keterlibatan kerja berpengaruh positif terhadap perilaku inovatif dan terbukti menjadi mediator yang menghubungkan kepemimpinan transformasional dengan inovasi guru. Sebaliknya, iklim sekolah tidak berpengaruh positif terhadap perilaku inovatif dan tidak memediasi hubungan tersebut. Secara keseluruhan, penelitian ini menegaskan bahwa untuk mendorong perilaku inovatif guru, sekolah perlu memperkuat praktik kepemimpinan transformasional yang humanis dan memberdayakan, serta menciptakan strategi yang meningkatkan keterlibatan kerja sebagai fondasi utama bagi munculnya inovasi.